Braille Innovation Technology in Teaching and Learning Process For Visual Impairment - Tisnawati, Nur Fadhilah; Yuliati; Endang Purbaningrum (JTP - Jurnal Teknologi Pendidikan, 2022)
The innovation of braille makes learning for children with visual impairments easier. The breakthrough braille innovation developed is able to encourage the creation of creative, active, and practical learning for children with visual impairments. This study aims to collect and analyze articles related to innovation technology of braille for teaching and learning process to visual impairment. The design of study used literature review that use data collection methods with search related topics, data analysis and also writing research results. The results of this study that braille innovations technology for reading, writing and conceptualizing of reading are useful in the learning process of children with visual impairments.